Perceived qualities of older workers and age management in companies. Issue 5 (3rd August 2015) - Principi, Andrea; Fabbietti, Paolo; Lamura, Giovanni
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – To explore whether the ages of human resources (HR) managers has an impact on their perceptions of the qualities/characteristics of older and younger workers (i.e., manager attitudes) and on the implementation of age management initiatives to the benefit of older workers (i.e., manager behaviors). The paper aims to discuss this issue. Design/methodology/approach – Based on theories concerning the origins of stereotypes and the concept of "in-group bias", three hypotheses were tested on a sample of HR managers from 516 Italian companies extracted from the Gfk Eurisko database by using factor analyses and bivariate and multivariate tools. Findings – The age of an HR manager seems to influence his/her attitudes towards older and younger workers, because HR managers judge workers of a similar age to them more positively. In contrast, the age of an HR manager does not seem to play a particular role in the implementation of age management initiatives. In the companies considered, however, there is a tendency to adopt early retirement schemes when the HR managers concerned are younger, while in general there is a tendency to implement age management initiatives and show a greater appreciation of older workers in larger companies. Practical implications – The implementation of age management initiatives to the benefit of older workers may improve HR managers ' perceptions of those workers ' positive qualities. Furthermore, specific training may help HR managers recognize that both younger and older workers have useful albeit different strengths. Originality/value – This study provides new empirical evidence from the Italian context on the largely under-investigated issue of the role played by age in shaping HR managers ' attitudes towards older workers, and age management policies in particular.